2010
DOI: 10.1007/s00520-010-0904-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistance training on quality of life in cancer: a systematic literature review and meta-analysis

Abstract: Existing evidence suggests that strength training programs for cancer survivors have marginal benefit. Further, fully powered studies are required to determine the optimal type, intensity, and timing of resistance training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 35 publications
6
28
2
1
Order By: Relevance
“…Following the PRET intervention, there were no statistically significant changes in QoL. Previous research suggests that QoL changes following PRET are typically modest in cancer survivors and patients with COPD [40,49]. The underpowered sample size and lack of control group make interpretation of these results tenuous; however, there could be several explanations for the lack of response observed here.…”
Section: Discussioncontrasting
confidence: 73%
“…Following the PRET intervention, there were no statistically significant changes in QoL. Previous research suggests that QoL changes following PRET are typically modest in cancer survivors and patients with COPD [40,49]. The underpowered sample size and lack of control group make interpretation of these results tenuous; however, there could be several explanations for the lack of response observed here.…”
Section: Discussioncontrasting
confidence: 73%
“…[13][14][15] A metaanalysis examining the effect of RET on QOL for all cancers reported a small clinical benefit from resistance exercise immediately post-intervention; 14 because few of the included studies reported follow-up data, however, the authors were not able to draw conclusions on longterm effects. 14 Our follow-up results show that benefits are largely sustained over the follow-up period and that further improvement may also occur in the subgroup of participants who continue regular RET.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is one of the first to provide follow-up data on a resistance exercise intervention for shoulder pain and dysfunction after neck dissection in HNC survivors. [13][14][15] Because the study design allowed crossover for participants originally assigned to the TP group, we did not anticipate continued group differences at 12-month follow-up based on randomization. We were interested to determine, however, whether any benefits from the 12-week PRET intervention persisted over the longer term.…”
Section: Ré Sumémentioning
confidence: 99%
“…System atic review s have docu m ented that strength exercise improves m any health outcom es in cancer survivors, including m uscular stren g th and en d u ran ce, lean body m ass, fatigue, and quality of life (Cheema, Gaul, Lane, & Fiatarone Singh, 2008;Cramp, James, & Lambert, 2010;DeBacker, Schep, Backx, Vreugdenhil, & Kuipers, 2009;Strasser, Steindorf, Wiskemann, & Ulrich, 2013). One trial even reported that strength exercise improved chemotherapy completion rate in patients w ith breast cancer (Cour neya et al, 2007).…”
mentioning
confidence: 95%